Relational Thinking Test Instrument Analysis: Transition from Arithmetic to Algebra - Andini, Meri; Jupri, Al; Kusumah, Yaya S. (Universitas Negeri Semarang, 2025)
Relational thinking, a cognitive approach bridging arithmetic thinking and algebraic thinking, has been developed by numerous researchers through mathematics learning processes to address students' difficulties in learning algebra. This study aims to develop a relational thinking test instrument for students and conduct both quantitative and qualitative analyses to measure relational thinking abilities in a valid and reliable manner. The research methodology adapts the development model proposed by Gall and Borg (2003) regarding the process of developing and validating products (test instruments), involving 64 seventh-grade students. Data analysis involved validity and reliability tests as well as analysis of students' written responses. The results indicate that the test instrument is valid (except for test item P8) and reliable, with a coefficient of α = 0.69 (high). Revisions were made to several items that were invalid or less valid based on quantitative and qualitative analysis. The revised instrument can be considered a good relational thinking test instrument, though it is recommended to support it with non-test results (such as interviews) to enhance accuracy and observe students' thinking consistency.